Mussel‐Inspired Polymerization of Peptides: The Chemical Activation Route as Key to Broaden the Sequential Space of Artificial Mussel‐Glue Proteins. Issue 1 (6th November 2019) - Kohn, Jana M.; Riedel, Jerome; Horsch, Justus; Stephanowitz, Heike; Börner, Hans G.
Abstract: A previously introduced tyrosinase‐activated polymerization of Tyr‐ and Cys‐bearing peptides yielding artificial mussel‐glue proteins is realized without the need of the specific enzyme by a chemical activation route. This decouples the sequence of polymerizable peptides (unimers) from the constraints of tyrosinase substrates and enables the polymerization of minimal motifs such as Dopa‐Lys‐Cys (Umini *KC ) or Dopa‐Gly‐Cys (Umini *GC ). In the polymerization procedure, sodium periodate is used to oxidize Dopa residues of the unimers to Dopa‐quinones to which the thiol of a Cys residue is added in a Michael‐type reaction. The resulting polyUmini *KC and polyUmini *GC exhibit a thiol–catechol connectivity as a potent adhesive functionality at each repeat unit. QCM‐D experiments show the excellent substrate adsorption properties of the products from the chemically activated polymerization. On aluminum oxide surfaces, polyUmini *KC rapidly forms a coating, even under seawater model conditions and the coating resists rinsing with hypersaline solution of 4.2 M salt mixtures. While the sodium periodate oxidation is less specific than the tyrosinase reaction and requires the implementation of Dopa instead of Tyr residues into the polymerizable unimers, the chemical route makes scale‐up more easily accessible. Abstract : A chemical activation route makes the use of tyrosinase in the mussel‐inspired polymerization of peptides obsolete and enables the exploitation of the sequence space to generate artificial mussel‐glue proteins. This is shown by polymerizing the minimal adsorption domain Dopa‐Lys‐Cys, leading to poly(Dopa‐Lys‐Cys) with non‐peptidic thiol–catechol connectivities in the backbone. Polymer films are formed under seawater conditions and resist washing with 4.2 M hypersaline solution.